Stage-Two Secularity and the Future of Theology-and-Science - Peterson, Gregory R. (Zygon, 2010)
Abstract. Charles Taylor has recently provided an in-depth exploration of secularity, with a central characteristic being the understanding that religious commitment is optional. This essay extends this analysis, considering the possibility that American society may be entering a second stage of secularity, one in which the possibility of religious commitment ceases to be an option at all for many. The possible implications of such a development are considered for the theology-and-science dialogue.